(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the use of authentic materials—texts, audio, and video—in enhancing English as a Foreign Language (EFL) learning. Authentic materials, defined as content originally created for native speakers, are often hailed for their potential to offer realistic language exposure and cultural insights. However, their integration into EFL classrooms raises both benefits and challenges. This article examines the advantages of using authentic materials in terms of linguistic skills development, motivation, and cultural understanding, while also addressing the challenges that teachers and learners face when employing such materials. Finally, recommendations for effective implementation are provided.